Here's the question you clicked on:
ewkmath
what is X when 2sin^2(X)+9cos(X)+3=0
have you subbed \(\sin^2 x x = 1-\cos^2 x\) into the eq to simplify it into a quadratic eq?
no i haven't but i'll try it out right now thanks :)
u r welcome. The solution should be trivial after the substitution. :)
I tried it but i still don't get it..
subbing, you should get, \(2-2\cos^2 x + 9 \cos x +3=0\) which equals, \(-2\cos^2 x + 9 \cos x +5=0\) let u = cos x the equation becomes \(-2u^2 + 9 u +5=0\) which is a quadratic equation of u. You can use the general formula to solve for u.
thanks o much.. i really appreciate it